Pengaruh Employee Branding terhadap Peran Karyawan dalam Membangun Loyalitas dan Reputasi Perusahaan - Setyawan, Arel Saputra; Ambarwati, Mega Dewi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Employee branding is a crucial strategy in modern organizations to strengthen employee loyalty and build the company’s reputation among the public. This study aims to analyze the impact of employee branding on employees' roles in fostering loyalty and enhancing corporate reputation. Using a quantitative approach, data were collected through surveys involving 200 employees from various industries. The findings reveal that employee branding has a positive and significant effect on employee engagement in promoting company values. Furthermore, this strategy also contributes to increased loyalty and a positive corporate image. The study concludes by highlighting the importance of employees' roles as brand ambassadors in fostering stronger relationships between companies and their customers.